Correlation between dengue-specific neutralizing antibodies and serum avidity in primary and secondary dengue virus 3 natural infections in humans. - Andreas Puschnik; Louis Lau; Elizabeth A Cromwell; Angel Balmaseda; Simona Zompi; Eva Harris (Public Library of Science (PLoS), 2013)
Although heterotypic secondary infection with dengue virus (DENV) is associated with severe disease, the majority of secondary infections are mild or asymptomatic. The mechanisms of antibody-mediated protection are poorly understood. In 2010, 108 DENV3-positive cases were enrolled in a pediatric hospital-based study in Managua, Nicaragua, with 61 primary and 47 secondary infections. We analyzed DENV-specific neutralization titers (NT50), IgM and IgG avidity, and antibody titer in serum samples collected during acute and convalescent phases and 3, 6, and 18 months post-infection. NT50 titers peaked at convalescence and decreased thereafter. IgG avidity to DENV3 significantly increased between convalescent and 3-month time-points in primary DENV infections and between the acute and convalescent phase in secondary DENV infections. While avidity to DENV2, a likely previous infecting serotype, was initially higher than avidity to DENV3 in secondary DENV infections, the opposite relation was observed 3-18 months post-infection. We found significant correlations between IgM avidity and NT50 in acute primary cases and between IgG avidity and NT50 in secondary DENV infections. In summary, our findings indicate that IgM antibodies likely play a role in early control of DENV infections. IgG serum avidity to DENV, analyzed for the first time in longitudinal samples, switches from targeting mainly cross-reactive serotype(s) to the current infecting serotype over time. Finally, serum avidity correlates with neutralization capacity.